Groups and Symmetry: A Guide to Discovering Mathematics - David W. Farmer (Mathematical world, v. 5., 1998)
In most mathematics textbooks, the most exciting part of mathematics - the process of invention and discovery - is completely hidden from the reader. The aim of Groups and Symmetry is to change that. By means of a series of carefully selected tasks, the book leads readers to discover groups and symmetry. There are no formulas to memorize; no procedures to follow. The book is a guide: its job is to start the reader in the right direction.